Mast cell stabilization with sodium cromoglycate modulates pulmonary vessel wall remodeling during four-day hypoxia in rats - Novotný, Tomáš; Krejčí, Jakub; Malíková, Jana; Švehlík, Vojtěch; Wasserbauer, Roman; Uhlík, Jiří; Vajner, Luděk (Experimental lung research, 2015)
AIM OF THE STUDY: In rats, the environment with low content of oxygen induces hypoxic pulmonary hypertension. Remodeling of pulmonary resistance arteries is particularly triggered by the mast cell degranulation products, e.g., rodent-like interstitial collagenase (matrix metalloproteinase 13). Administration of sodium cromoglycate leads to stabilization of mast cell granules, and thus to the modified remodeling process. MATERIALS AND METHODS: During four-day hypoxia, we treated rats with sodium cromoglycate. Pulmonary vascular remodeling was assessed as well as counts of periarterial pulmonary mast cells, both total and matrix metalloproteinase 13-positive ones. RESULTS: Four-day hypoxia induced remodeling of both resistance arteries and large conduit arteries. We have found increase in the tunica media thickness of resistance arteries. Tunica adventitia thickness of both resistance arteries and large conduit arteries with a diameter of over 300 μm increased as well; the latter ones revealed increase in the number of vasa vasorum in their walls. Mast cell stabilization suppressed hypoxic pulmonary vascular remodeling in resistance pulmonary arteries. Four-day hypoxia led to changes in distribution of toluidine blue-detected and MMP-13 positive periarterial mast cells; this redistribution was also influenced by the administration of sodium cromoglycate. CONCLUSIONS: The number of pulmonary periarterial mast cells seemingly decreases during hypoxia due to their degranulation, which disables their identification. Large conduit arteries do not affect final blood pressure in the pulmonary vascular bed; however, their structure changes substantially under hypoxia. Such remodeling changes are not mediated by mast cell products only since they have occurred in spite of stabilization of mast cell granules.
Keywords: hypoxic pulmonary hypertension; mastocyty; Animals; Mast Cells; Hypoxia; Lung; Rats, Wistar; Hypertension, Pulmonary; arteria pulmonalis; matrix metalloproteinase 13; kromoglykát dvojsodný; Pulmonary Artery; morphometry; hypoxie; matrixová metaloproteinasa 13; Male; Oxygen; Cromolyn Sodium; krysa rodu Rattus; plíce; plicní hypertenze; zvířata; mužské pohlaví; normobaric hypoxia; Rats; Matrix Metalloproteinase 13; kyslík; potkani Wistar